THE LEGAL NATURE OF PUBLIC REPRESENTATIVES' PARTICIPATION IN LEGISLATIVE ACTIVITY: INTERNATIONAL STANDARDS AND FOREIGN EXPERIENCE - Saida Abdimalikova (Innovate Conferences, 2025)
This paper explores the legal nature of public representatives’ participation in legislative activity as a democratic imperative rooted in the principle of popular sovereignty. The study examines how this participation is recognized both as a fundamental human right and as a mechanism for ensuring transparency, accountability, and inclusiveness in lawmaking. Drawing on international legal instruments—including the International Covenant on Civil and Political Rights (ICCPR), the guidelines of the United Nations, OSCE/ODIHR, and IDEA—the research highlights key global standards supporting participatory legislative processes. It also analyzes recent constitutional and legislative reforms in Uzbekistan, particularly after the 2023 amendments, which have increasingly institutionalized public involvement in governance.
Keywords: Public Participation, Legislative Process, Popular Sovereignty, International Law, Human Rights, Uzbekistan, Democratic Governance, ICCPR, OSCE/ODIHR, Constitutional Reform, SDG 16, Civil Society, Legal Mechanisms